Potassium Fertilizer Recommendations for Sugarcane on Florida Mineral Soils - J. Mabry McCray (EDIS)
This publication is intended primarily for Florida sugarcane growers, but it may also be useful to researchers and others interested in sugarcane nutrition. It presents potassium fertilizer recommendations for Florida mineral soils and supporting information. Written by J. Mabry McCray, and published by the UF/IFAS Agronomy Department, September 2022.